(untitled) (Bangladesh Heart Journal, 2023)
Background: Tricuspid annular plane systolic excursion (TAPSE) is an Echocardiographic measure that allows us to assess right ventricular systolic function and it correlates well with reference techniques like Cardiac Magnetic Resonance Imaging. TAPSE measurement is common in adults. Objective: Our objective was to determine values of TAPSE in Bangladeshi adults with or without LV systolic dysfunction and to determine the relationship of these values with age, sex, RVIDd, LVEF & EPSS. Method: This was an prospective observational study in patients undergoing comprehensive transthoracic echocardiography for any indication. From April 2022 to April 2023 we prospectively enrolled 100 adult (from 30 to age 80 years) of both sexes who presented to the Cardiology Clinic of LABAID Cardiac Hospital. We performed a complete transthoracic echocardiography study. We measured TAPSE in 2-dimensional M-mode echocardiograms from the apical 4- chamber view, positioning the cursor on the lateral tricuspid annulus near the free RV wall and aligning it as close as possible to the apex of the heart . The mean values were taken by at least 2 measurements for reducing interobserver and intraobserver variability’s. Patients with confirmed congenital & valvular heart disease were excluded. Results: Mean TAPSE values were 19.15±3.87cm irrespective of LVEF, with no significant differences between sexes, 18.45±3.801 in male , 19.94±3.853 in female (P=.056). TAPSE value was 22.00±1.581 in person with normal LVEF & 16.77±2.455 in person with reduced LVEF ( P<.001) A statistically significant positive correlation of LVEF (r=.813) and significant negative correlation of EPSS (r=-.639) were observed with TAPSE (p<0.001). But no significant correlation of TAPSE was found between age (r=-.185)). ), gender (r=.192) & RVIDd (r= -.063) (p >0.05). Multivariate analysis confirmed these correlations and the interactions between variables (LVEF & EPSS). Graphs of estimated population-based TAPSE values adjusted by age and LV function are provided. Conclusion: We determined values of TAPSE in Bangladeshi adult population with or without LV systolic dysfunction and assessed relationship of these values with age, sex, RVIDd, LVEF & EPSS. The TAPSE measurement was reproducible and associated directly with LV systolic function. These reference values could guide decision making in daily clinical practice. Bangladesh Heart Journal 2023; 38(2): 92-101